Feeding ecology of carnivores (Mammalia, Carnivora) in Atlantic Forest remnants, Southern Brazil. - ROCHA-MENDES, F. (2010)
The diet of some sympatric carnivore species in three Atlantic Forest remnants of Southern Brazil was studied in order to assess their food niche. We conducted monthly field trips between February 2003 and January 2004 to collect fecal samples that were subsequently examined together with others collected sporadically between November 1994 and January 2003. Of the 416 samples analysed, 198 had the “author” species identified through microscopic analysis guard hairs, which revealed the presence of 10 carnivores and some information about their diet. Puma yagouaroundi had the largest dietary niche breadth, whereas Leopardus tigrinus and Nasua nasua showed the lowest values. Extensive niche overlap was observed between L. tigrinus and N. nasua, L. tigrinus and L. wiedii, and between L. tigrinus and L. pardalis. Data presented here not only increases the understanding of carnivore feeding ecology, but also contributes towards their conservation in the study region and other fragmented landscapes in Brazil and neighboring countries.